Self-Efficacy and Social Support as Determinants of Resilience in Post-Stroke Patients - Faradisa, Elok; Kusumawati, Mira Wahyu; Budiman, Amin Aji; Listyaningrum, Desy (Yayasan Jompa Research and Development, 2025)
Stroke is a leading cause of long-term disability that profoundly impacts the physical and psychological well-being of survivors. Psychological resilience is a crucial adaptive capacity that facilitates recovery in post-stroke patients. This study aimed to examine the relationships between self-efficacy, social support, and resilience among post-stroke survivors. A cross-sectional study was conducted involving 84 stroke patients attending the Neurology Clinic at a general hospital in Surakarta. Participants were selected using purposive sampling. Data were collected using the Stroke Self-Efficacy Questionnaire (SSEQ), the Multidimensional Scale of Perceived Social Support (MSPSS), and the 10-item Connor-Davidson Resilience Scale (CD-RISC 10). Spearman’s correlation analysis was applied to assess the relationships between variables. The results indicated a significant positive correlation between self-efficacy and resilience (p < 0.01; r = 0.572). Social support was also positively correlated with resilience, though with a smaller effect size (p < 0.01; r = 0.296). Conclusion both self-efficacy and social support play significant roles in enhancing resilience among post-stroke survivors. Nursing interventions aimed at enhancing self-efficacy and reinforcing social support are essential for improving resilience in post-stroke survivors.